In Vitro Propagation of Medicinal Plant Orthosiphun Stamineus (Misai Kucing) Through Axillary Branching and Callus Culture - Kamaludin, Rashid; Arash, Nezhadahmadi; Roihan, Mohsin; Shamrulazhar, Shamzir Kamal; Shahril, Efzueni (Marsland Press / Zhengzhou University, 2012)
Orthosiphun stamineus is a herbaceous plant that is popularly known as Misai Kucing. It is widely used in traditional medicine as diuretic agent. This study was divided into two parts that was the in vitro production of complete plantlet through axillary branching and callus culture derived from leaf explant. In axillary branching method, sterilization was conducted using 0.02mg/100ml of mercuric chloride followed by rinsing with 20% and 50% of Clorox for 20 minutes and 5 minutes respectively. This sterilization method was able to remove the contaminants from the surface of the axillary stem and almost 70% of the explants were survived. Axillary bud was placed on Murashige and Skoog (MS) basic medium and cultured for 1 month. The in vitro shoot was inoculated on MS medium which was supplemented with different concentrations of BAP and NAA. The medium that contained 1.0mg/L of BAP gave the best shoot multiplication (13.25) and shoot length (6.23cm) after 8 weeks in culture. Root formation in term of percentage of root (70%) and the number of root produced (10.50) were the best when shoot inserted into medium contained 6mg/L IBA after 3 weeks in culture. However, MS medium that was supplemented with 2 mg/L IBA enhanced in the root length (3.85 cm). Meanwhile, in callus culture, the leaf explant was placed on MS medium containing with various concentrations of 2,4-D for induction of callus. The optimum level of callus induction and proliferation rate (0.42) were obtained with 4mg/L 2,4-D. The callus cells were tested in medium with Evan’s Blue staining and the result showed that the cells were embryogenic. However, the shoot induction from the callus was failed in all tested mediums containing different combinations of BAP and 2,4-D.